THE COMPREHENSIVE SYSTEMATIC REVIEW OF ASSOCIATION OF POOR GLYCEMIC CONTROL (HBA1C) TO THE DEVELOPMENT OF MICROVASCULAR COMPLICATIONS IN DIABETES - Fabian G.S; M. Rizki F (Jurnal Kesehatan Siliwangi, 2025)
Introduction: Diabetes mellitus remains a major global health challenge, with microvascular complications—retinopathy, nephropathy, and neuropathy—contributing significantly to morbidity and reduced quality of life. Glycemic control, primarily measured by HbA1c, is a cornerstone of diabetes management, but the strength and consistency of its association with microvascular outcomes across diabetes types and patient subgroups require comprehensive synthesis. Methods: We conducted a systematic review of 80 studies investigating the association between HbA1c and microvascular complications in Type 1 and Type 2 diabetes. Studies were screened based on predefined criteria including study design, population, measurement of HbA1c, assessment of microvascular outcomes, and availability of quantitative data. Data were extracted on HbA1c definitions, complication types, study characteristics, effect measures, and confounding control. Results: Poor glycemic control (HbA1c >7%) was consistently associated with increased risk and progression of microvascular complications. In Type 1 diabetes, intensive control reduced retinopathy by 76%, nephropathy by 39–56%, and completely prevented clinical neuropathy over 24 years. In Type 2 diabetes, intensive control reduced retinopathy progression by 23–33% and nephropathy by 21–26%. However, benefits diminished in older patients, those with advanced complications, or long disease duration. Glycemic variability and metabolic memory effects were also significant. Intensive control increased severe hypoglycemia risk approximately twofold. Discussion: The association between HbA1c and microvascular complications is strong but modulated by diabetes type, disease stage, age, and glycemic variability. Early intensive control yields lasting benefits via metabolic memory, especially in Type 1 diabetes. In Type 2 diabetes, individualized targets are essential to balance microvascular benefits against hypoglycemia and mortality risks. Conclusion: Glycemic control is fundamentally important in preventing and delaying microvascular complications, but treatment must be personalized. Future research should focus on variability metrics, early intervention windows, and integrative management strategies.